GOOD CORPORATE GOVERNANCE, GREEN ACCOUNTING, AND EARNINGS SUSTAINABILITY: EVIDENCE FROM JAKARTA ISLAMIC INDEX - Rokhaniyah, Siti; Khotijah, Siti Afidatul; Manurung, Herlina; Permatasari, Desi; Anisyawati, Anisyawati (Fakultas Ekonomi dan Bisnis, UNTAN, 2024)
This research examines the influence of good corporate governance (GCG) practices on the earnings sustainability of companies listed in the Jakarta Islamic Index. Additionally, it explores the role of green accounting in the relationship between GCG and sustainable earnings. GCG is represented by management ownership, boards of commissioners, the audit committee, and institutional ownership. Green accounting is measured using the corporate environmental management (PROPER) results, which are aligned with the regulations of the Ministry of Environment and Forestry of Indonesia. Data analysis was carried out using panel data regression analysis. The findings indicate that GCG components (management ownership, boards of commissioners, and audit committee) positively impact sustainable earnings. Moreover, green accounting has been empirically proven to moderate the positive effect of GCS on sustainable earnings. Based on the sustainability theory, companies tend to undertake ethical and legal measures to achieve sustainable performance. Thus, sustainability theory suggests that the synergy between corporate governance and green accounting may improve earnings sustainability.JEL: M14, M41, L25.